A thermal insulation gradient composite material with controllable surface density and preparation method thereof
By forming a dense layer on the surface of the fiber prefabricated body and adjusting the density, and forming a density gradient structure in combination with the sol-gel process, the existing thermal protection materials are solved inadequate performance in extreme environments, and efficient anti-heat insulation and ablation effects are achieved.
Patent Information
- Application Number
- CN202410850229.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-06-28
- Publication Date
- 2025-04-25
- Estimated Expiration
- 2044-06-28
AI Technical Summary
Existing thermal protection materials are difficult to maintain the aerodynamic shape of the aircraft in extreme service environments, and the high weight of high-density materials is not conducive to weight loss. The ceramic coating is prone to cracking or falling off at high temperatures, resulting in the failure of the heat-proof function.
Hot melted phenolic resin is used to blend it with ceramic filler, and a dense layer is formed on the surface of the fiber preform through vacuum bag pressing. The density of the dense layer is controlled by the addition ratio of solvent and ceramic filler, and a density gradient structure is formed in combination with the sol-gel process.
It realizes controllable adjustment of surface density, improves the anti-heat insulation and ablation performance of the material, and is suitable for aerospace and nuclear industry.
Smart Images

Figure CN118852717B_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of composite materials, and in particular relates to a thermal insulation gradient composite material with controllable surface density and a preparation method thereof. Background Art
[0002] With the further development of deep space exploration, spacecraft will face more severe aerodynamic thermal environment when entering planets and re-entering the Earth's atmosphere; at the same time, in the field of aerospace, the Mach number of hypersonic vehicles continues to increase, not only will the outer surface of the aircraft face severe aerodynamic heating, but the aircraft engine also needs higher temperature to provide a high thrust-to-weight ratio. These service environments have put forward requirements for existing thermal protection materials to be lightweight, highly heat-insulating, low-ablative, and long-lasting.
[0003] Current low-density aerogel ablative insulation materials have the characteristics of high thermal insulation and light weight, but the ablation retreat rate is large (linear ablation rate is large), and it is difficult to maintain the aerodynamic shape of the aircraft under extreme service environments. Although high-density carbon phenolic or silicone rubber materials have good ablation resistance, they have high density and heavy weight, which is not conducive to the weight reduction needs of aircraft. Spraying ceramic coatings on the surface of low-density aerogel ablative insulation materials to prepare gradient structural materials is a commonly used process for obtaining thermal insulation materials. However, due to the thermal stress mismatch between the external ceramic coating and the internal low-density aerogel at high temperatures, the ceramic coating is prone to cracking or even falling off, resulting in failure of the heat protection function. Chinese patent application CN 116118222 A discloses a ceramic heat-insulating composite material and a preparation method thereof. The ceramic heat-insulating composite material is divided into an inner quartz fiber cloth / ceramic resin heat-insulating layer and an outer quartz fiber mesh cloth / ceramic resin heat-insulating layer, and is formed by a semi-curing-molding co-curing process. First, the inner quartz fiber cloth / ceramic resin heat-insulating layer is pre-cured by a vacuum semi-curing process, and then the surface of the inner quartz fiber cloth / ceramic resin heat-insulating layer is covered with a quartz fiber mesh cloth / ceramic resin prepreg. Finally, an integrated composite material with a heat-proof function in the inner layer and a heat-insulating function in the outer layer is obtained by a molding co-curing process. However, the material prepared in this way is formed by stacking multiple layers of prepregs, and finally the inner heat-proof layer and the outer heat-insulating layer need to be composited together by molding co-curing. However, there may be an incomplete interface bonding problem between different layers. Even after curing, the interface bonding strength between different layers is not enough to achieve an ideal integration effect. There may be a weak bonding area at the interface, which affects the overall performance of the material.
[0004] In view of the above problems, it is very necessary to develop an integrated thermal protection material with dense surface and internal insulation, and at the same time, it is necessary to regulate the density of the dense surface layer to achieve performance optimization for different service environments. Summary of the invention
[0005] In order to solve one or more technical problems existing in the prior art, the present invention provides a thermal insulation gradient composite material with controllable surface density and a preparation method thereof. The thermal insulation gradient composite material with controllable surface density prepared by the present invention has excellent thermal insulation performance and anti-ablation performance, and can realize controllable adjustment of surface density, and can be applied to thermal protection fields requiring excellent thermal insulation performance such as aerospace and nuclear industry.
[0006] In a first aspect, the present invention provides a method for preparing a thermal insulation gradient composite material with controllable surface density, the method comprising the following steps:
[0007] (1) mixing a hot-melt phenolic resin, a ceramic filler and a solvent at 40 to 90° C. to obtain a premix, and coating the premix on a release paper using a coating machine to obtain a mixed film;
[0008] (2) laying the mixed film on one side of the fiber preform and impregnating the mixed film into the fiber preform by using a vacuum bag pressing process; repeating this step until the premix impregnated into the fiber preform reaches a preset impregnation thickness, and the impregnation is completed;
[0009] (3) curing the impregnated fiber preform at 100 to 200° C. to obtain a fiber preform with controllable surface density;
[0010] (4) preparing a phenolic resin solution, then impregnating a fiber preform with controllable surface density with the phenolic resin solution, and then sequentially performing sol-gel, solvent replacement and normal pressure drying to obtain a thermal insulation gradient composite material with controllable surface density.
[0011] Preferably, in step (2), the multilayer mixed film is sequentially impregnated into the fiber preform, and the impregnation thickness is regulated by the mixed film thickness and the number of impregnations; in step (1), the surface density of the fiber preform is regulated by regulating the addition ratio of the ceramic filler and the solvent in the premix.
[0012] Preferably, the hot-melt phenolic resin is a pre-polyphenolic resin that can melt at 40-90°C and cure at 100-200°C.
[0013] Preferably, the ceramic filler is at least one of a silicon-based filler, a boron-based filler, a carbon-based filler and an oxide-based filler. Preferably, the ceramic filler is at least one of mica, zirconium diboride, boron carbide and silicon carbide; the particle size of the ceramic filler is 0.1-10 μm; and / or the mass fraction of the ceramic filler in the premix is 1 to 30 wt%.
[0014] Preferably, the solvent is ethanol and / or ethylene glycol; and / or the mass fraction of the solvent contained in the premix is 0 to 30 wt %.
[0015] Preferably, the thickness of the mixed film is 0.1-2 mm; and / or the impregnation thickness of the premix in the fiber preform is 1-10 mm.
[0016] Preferably, the fiber preform is at least one of a carbon fiber preform, a quartz fiber preform, a mullite fiber preform, and a glass fiber preform; and / or the structure of the fiber preform is at least one of a fiber needle felt, a 2.5D fabric, and a 3D fabric.
[0017] Preferably, the processing temperature of the vacuum bag pressing process is 40 to 90° C., the vacuum degree is -0.03 to -0.1 MPa, and the processing time is 5 to 60 min; and / or the curing treatment time is 2 to 10 h.
[0018] Preferably, the anti-insulation gradient composite material with controllable surface density comprises a density gradient structure consisting of a dense layer and an insulation layer formed in a fiber preform; the density of the insulation layer is 0.2 to 0.5 g / cm 3 The density of the dense layer is 0.89-1.31 g / cm 3 .
[0019] In a second aspect, the present invention provides a thermal insulation gradient composite material with controllable surface density, which is prepared by the preparation method described in the first aspect of the present invention.
[0020] Compared with the prior art, the present invention has at least the following beneficial effects:
[0021] (1) The present invention adopts hot-melt phenolic resin and impregnates it into the fiber preform by vacuum bag pressing process, so as to form a dense surface layer on the surface of the fiber preform. At the same time, the density of the dense layer is regulated by the addition ratio of solvent and ceramic filler, so that the performance design and optimization can be better carried out according to the service environment.
[0022] (2) The present invention uses hot-melt phenolic resin to form a film and impregnate it into the fiber preform layer by layer. The thickness of the dense layer on the surface of the fiber preform can be accurately controlled by controlling the thickness of the mixed film and the number of layers of the mixed film impregnated into the fiber preform. At the same time, by utilizing the vacuum bag pressing process and the adaptability of the mixed film to the surface shape of the fiber preform, a dense layer can be formed on the surface of various special-shaped components, which has excellent processability and expansibility.
[0023] (3) The present invention uses hot-melt phenolic resin and ceramic filler to blend and impregnate into the fiber preform. Compared with the existing solution impregnation method, the hot-melt phenolic resin has a higher viscosity and has a greater adhesive force on the ceramic filler during impregnation, thereby driving the ceramic filler to flow into the fiber preform, and then a high content of ceramic filler can be added to the surface dense layer and a more uniform distribution of the ceramic filler in the thickness direction can be achieved; and the high content and uniform distribution of ceramic filler in the dense layer can promote the ceramic transformation of the surface ceramicizable anti-insulation gradient composite material at high temperature, thereby obtaining better anti-ablation and oxygen isolation properties. BRIEF DESCRIPTION OF THE DRAWINGS
[0024] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0025] Figure 1 It is a flow chart of a method for preparing a gradient anti-insulation composite material with controllable surface density provided by the present invention;
[0026] Figure 2 is a schematic diagram of the vacuum bag pressure impregnation process used in the present invention;
[0027] Figure 3 It is a schematic structural diagram of a thermal insulation gradient composite material with controllable surface density provided by the present invention;
[0028] Figure 4 This is a diagram of a special-shaped component of a thermal insulation gradient composite material with controllable surface density provided by the present invention;
[0029] Figure 5 This is an electron microscope image of the surface dense layer of the anti-thermal insulation gradient composite material with controllable surface density provided in Example 1 of the present invention;
[0030] Figure 6 This is an electron microscope image of the internal heat insulation layer of the heat-insulating gradient composite material with controllable surface density provided in Example 1 of the present invention;
[0031] Figure 7 This is a picture of the ablated surface of the thermal insulation gradient composite material with controllable surface density provided by the present invention after an oxyacetylene ablation test;
[0032] Figure 8 This is a picture of the ablation cross section of the anti-insulation gradient composite material with controllable surface density provided by the present invention after an oxyacetylene ablation test. DETAILED DESCRIPTION
[0033] In order to make the purpose, technical solution and advantages of the present invention clearer, the technical solution of the present invention will be clearly and completely described below in combination with the embodiments of the present invention. Obviously, the described embodiments are part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0034] In a first aspect, the present invention provides a method for preparing a thermal insulation gradient composite material with controllable surface density, the method comprising the following steps:
[0035] (1) mixing a hot-melt phenolic resin, a ceramic filler and a solvent at 40 to 90° C. (for example, 40° C., 50° C., 60° C., 70° C., 80° C. or 90° C.) to obtain a premix, and coating the premix on a release paper using a coating machine to obtain a mixed film;
[0036] (2) laying the mixed film on one side of the fiber preform and impregnating the mixed film into the fiber preform by a vacuum bag pressing process (also referred to as a vacuum bag pressing impregnation process); repeating this step until the premix impregnated into the fiber preform reaches a preset impregnation thickness, and the impregnation is completed;
[0037] (3) curing the impregnated fiber preform at 100 to 200° C. (for example, 100° C., 120° C., 140° C., 160° C., 180° C. or 200° C.) to obtain a fiber preform with controllable surface density;
[0038] (4) preparing a phenolic resin solution, then impregnating a fiber preform with controllable surface density with the phenolic resin solution, and then sequentially subjecting the preform to sol-gel, solvent replacement and normal pressure drying to obtain a thermal insulation gradient composite material with controllable surface density; that is, step (4) is: in-situ forming a phenolic aerogel inside the fiber preform with controllable surface density obtained in step (3), and forming a thermal insulation layer after vacuum impregnation, sol-gel process, solvent replacement and normal pressure drying, thereby obtaining a thermal insulation gradient composite material with controllable surface density; in this In the present invention, when performing the impregnation in step (4), for example, the fiber preform with controllable surface density can be immersed in a phenolic resin solution as a whole for vacuum impregnation. Since the fiber preform with controllable surface density has no premix in the thickness direction except for the impregnation thickness portion reached by the premix (i.e., the thickness portion forming the surface dense layer), the other portions are not impregnated with the premix. The portion not impregnated with the premix can be impregnated with the phenolic resin solution, thereby realizing the in-situ formation of the phenolic aerogel inside and obtaining a heat insulating layer inside the fiber preform.
[0039] In the present invention, hot-melt phenolic resin, ceramic filler and solvent are uniformly mixed at 40-90°C and coated on release paper by a coating machine to obtain a mixed film. This process ensures the uniform distribution of hot-melt phenolic resin and ceramic filler, laying a foundation for subsequent uniform impregnation. The present invention spreads the mixed film on the fiber preform and impregnates it into the fiber preform by vacuum bag pressing. The repeated operation of this step ensures the uniform distribution of the premix in the fiber preform. The thickness of the dense layer on the surface of the fiber preform can be accurately controlled by controlling the thickness of the mixed film and the number of layers of the mixed film impregnated with the fiber preform. At the same time, the vacuum bag pressing process and the adaptability of the mixed film to the surface shape of the fiber preform can be used to impregnate the fiber preform on the surface of various special-shaped components. The dense layer is formed, which has excellent processability and scalability. Compared with the molding of a single membrane, the edge effect can be effectively avoided, and the controlled matching of unequal-surface configuration structures can be achieved. The mixed membrane obtained by the present invention contains a solvent, and the solvent basically does not volatilize in the mixed membrane stage and the impregnation stage, but when solidified at 100-200°C, the solvent will volatilize, which can leave a uniform porous structure inside the fiber preform, and realize the regulation of the density of the dense layer by adding solvents and ceramic fillers, which can better design and optimize the performance according to the service environment, and the fiber preform after impregnation is solidified at 100-200°C to form a fiber preform with controllable surface density. This process further enhances the bonding between the hot-melt phenolic resin and the fiber through heat treatment. The composite strength is improved, and the density of the surface dense layer is improved; finally, the present invention adopts the method of in-situ forming phenolic aerogel inside the fiber preform, so that the surface density controllable thermal insulation gradient composite material has a density gradient structure composed of a dense layer and a thermal insulation layer formed in the fiber preform, so that the interior of the material (thermal insulation layer) has a lower density to provide thermal insulation performance, and the surface (dense layer) has a higher density to provide heat protection performance; since the material of the present invention is based on the surface densification and internal thermal insulation of the same fiber preform during the manufacturing process, there is no obvious interface layer bonding structure, and an integrated material with a stable overall structure is formed. Compared with multi-layer composite materials, the overall structural material has better stability and is not prone to delamination or peeling. It helps to maintain the consistency of thermal expansion under the action of thermal stress and reduce the internal stress and cracking risks caused by differences in thermal expansion coefficients at different levels; the anti-thermal insulation gradient composite material with controllable surface density described in the present invention includes a density gradient structure composed of a dense layer and a thermal insulation layer formed in the fiber preform, which optimizes the thermal insulation properties of the material, so that the surface of the material has a higher density and compactness, which can effectively prevent heat conduction and heat intrusion, while the lower internal density provides good thermal insulation performance, reducing the speed and intensity of heat conduction to the inside; the anti-thermal insulation gradient composite material with controllable surface density described in the present invention has achieved true integration in structure and performance, and has high overall stability, thermal expansion consistency and optimized thermal insulation properties.
[0040] The present invention adopts hot-melt phenolic resin and ceramic filler to blend and impregnate into the fiber preform. Compared with the existing solution impregnation method, the hot-melt phenolic resin has higher viscosity and has greater viscosity for the ceramic filler during impregnation, thereby driving the ceramic filler to flow into the fiber preform, and then a high content of ceramic filler can be added to the surface dense layer and a more uniform distribution of the ceramic filler in the thickness direction can be achieved; and the high content and uniform distribution of ceramic filler in the dense layer can promote the ceramic transformation of the surface ceramicizable anti-insulation gradient composite material at high temperature, thereby obtaining better anti-ablation and oxygen isolation properties.
[0041] According to some preferred embodiments, in step (2), the multilayer mixed film is sequentially impregnated into the fiber preform, and the impregnation thickness is regulated by the mixed film thickness and the number of impregnations; in step (1), the surface density of the fiber preform is regulated by regulating the addition ratio of the ceramic filler and the solvent in the premix.
[0042] According to some specific embodiments, for example, Figure 1 As shown, the preparation method of the thermal insulation gradient composite material with controllable surface density comprises the following steps:
[0043] ① Weigh the hot-melt phenolic resin, ceramic filler and solvent in proportion, stir and mix them evenly under heating conditions to obtain a premix, and coat the premix on release paper with a coater to obtain a mixed film with uniform thickness;
[0044] ② Laying the mixed film obtained in step ① on one side of the fiber preform, and impregnating the mixed film into the fiber preform by using a vacuum bag pressing process; repeating this step, impregnating multiple layers of mixed film into the fiber preform layer by layer, and completing the impregnation; adjusting the impregnation thickness by the thickness of the mixed film and the number of impregnations, and adjusting the density by the addition ratio of the ceramic filler and the solvent;
[0045] ③ Curing the impregnated fiber preform to obtain a fiber preform with controllable surface density;
[0046] ④ In the fiber preform with controllable surface density obtained in step ③, phenolic aerogel is in-situ formed by the sol-gel process, and a thermal insulation layer is formed after vacuum impregnation, sol-gel process, solvent replacement and normal pressure drying, thereby obtaining a thermal insulation gradient composite material with controllable surface density.
[0047] In the present invention, a dense layer is prepared on the surface of a fiber preform by using film laying and vacuum bag pressing processes. The addition of solvents and ceramic fillers can regulate the density of the dense layer. The layer-by-layer film laying process makes the thickness of the dense layer controllable. The contour characteristics of the vacuum bag pressing process can prepare a dense layer on the surface of a large-sized special-shaped component, and ceramic fillers are blended in the dense layer to achieve better anti-ablation performance. The present invention also uses a sol-gel process to prepare a phenolic aerogel insulation layer, forming a density gradient structure in the fiber preform, and forming an integrated anti-insulation composite material with light weight and anti-ablation.
[0048] According to some preferred embodiments, the hot-melt phenolic resin is a pre-polymerized phenolic resin that can melt at 40-90°C and can be cured at 100-200°C; in the present invention, the hot-melt phenolic resin is a pre-polymerized phenolic resin that can melt at 40-90°C and can be cured at 100-200°C. Melting at 40°C-90°C can facilitate the selection of the mixing process between the ceramic filler and the hot-melt phenolic resin. If the temperature exceeds 100°C, the hot-melt phenolic resin will solidify and cannot be mixed with the ceramic powder. If the melting temperature of the selected hot-melt phenolic resin is too low, such as it can melt and flow at room temperature, it will be inconvenient to store it after film formation. In the present invention, it is preferred that the hot-melt phenolic resin melts at a temperature higher than room temperature but lower than 100°C to have fluidity, which facilitates the mixing of the hot-melt phenolic resin and the ceramic powder and the film laying process. The present invention finds that the viscosity of ordinary phenolic resin changes little with temperature, and the difference in viscosity between room temperature and 40-90°C is small. The viscosity that can form a film at room temperature cannot flow at high temperature and cannot be impregnated into the fiber preform; while the viscosity that can flow at high temperature cannot form a stable film at low temperature. The present invention finds during the research process that if liquid phenolic resin is used for experiments, the liquid phenolic resin still has fluidity at room temperature with the addition of ceramic filler, and cannot maintain the shape of the film. If a film is to be formed, the content of the ceramic filler needs to be more than 50wt%, but at this time the film does not have fluidity under heating conditions and cannot enter the fiber preform, and the present invention cannot be realized.
[0049] According to some preferred embodiments, the ceramic filler is at least one of a silicon-based filler, a boron-based filler, a carbon-based filler and an oxide-based filler. Preferably, the ceramic filler is at least one of mica, zirconium diboride, boron carbide and silicon carbide; it should be noted that at least one is a mixture of any one or any several in any proportion; the present invention has no special requirements for the particle size of the ceramic filler, and those skilled in the art can choose according to needs. Preferably, the particle size of the ceramic filler is 0.1-10μm (for example, it can be 0.1μm, 0.5μm, 1μm, 3μm, 5μm, 8μm or 10μm); and / or the mass fraction of the ceramic filler contained in the premix is 1-30wt% (for example, it can be 5wt%, 10wt%, 15wt%, 20wt%, 25wt%, 30wt%).
[0050] According to some preferred embodiments, the solvent is a good solvent for phenolic resins such as ethanol and ethylene glycol, preferably, the solvent is ethanol and / or ethylene glycol; and / or the mass fraction of the solvent contained in the premix is 0 to 30 wt% (for example, it can be 0 wt%, 5 wt%, 10 wt%, 15 wt%, 20 wt%, 25 wt% or 30 wt%); in the present invention, the mass fraction of the solvent contained in the premix should not exceed 30 wt%. The present invention finds that when the solvent content is too high, the viscosity of the premix will be too low, which will result in the inability to maintain the shape of the film at room temperature.
[0051] According to some preferred embodiments, the thickness of the mixed film is 0.1 to 2 mm (for example, it can be 0.1 mm, 0.3 mm, 0.6 mm, 0.9 mm, 1.2 mm, 1.5 mm, 1.8 mm or 2 mm); and / or the impregnation thickness of the premix in the fiber preform is 1 to 10 mm (for example, it can be 1 mm, 2 mm, 3 mm, 4 mm, 5 mm, 6 mm, 7 mm, 8 mm, 9 mm or 10 mm). In the present invention, preferably, the impregnation thickness of the premix in the fiber preform is 1 to 10 mm. If the impregnation thickness is too large, on the one hand, it will lead to an increase in the overall density of the material, and on the other hand, it will cause the ceramic filler to be too unevenly distributed in the thickness direction.
[0052] According to some preferred embodiments, the fiber preform is at least one of a carbon fiber preform, a quartz fiber preform, a mullite fiber preform, and a glass fiber preform; and / or the structure of the fiber preform is at least one of a fiber needle felt, a 2.5D fabric, and a 3D fabric.
[0053] According to some preferred embodiments, the processing temperature of the vacuum bag pressing process is 40-90°C (for example, it can be 40°C, 50°C, 60°C, 70°C, 80°C or 90°C), the vacuum degree is -0.03-0.1MPa (for example, it can be -0.03MPa, -0.04MPa, -0.05MPa, -0.06MPa, -0.07MPa, -0.08MPa, -0.09MPa or -0.1MPa), the processing time is 5-60min (for example, it can be 5min, 10min, 15min, 20min, 30min, 40min, 50min or 60min); and / or the curing treatment time is 2-10h (for example, it can be 2h, 3h, 4h, 5h, 6h, 7h, 8h, 9h or 10h).
[0054] According to some preferred embodiments, the surface density controllable thermal insulation gradient composite material comprises a density gradient structure consisting of a dense layer and a thermal insulation layer formed in a fiber preform; in the present invention, the thermal insulation layer is a thermal insulation layer filled with phenolic aerogel; the density of the thermal insulation layer is 0.2 to 0.5 g / cm 3 (For example, it can be 0.2g / cm 3 , 0.25g / cm 3 , 0.3g / cm 3 , 0.35g / cm 3 , 0.4g / cm 3 , 0.45g / cm 3 or 0.5g / cm 3 ); the density of the dense layer (surface dense layer) is 0.89 to 1.31 g / cm 3 (For example, it can be 0.89 g / cm 3 , 0.92g / cm 3 , 0.94g / cm 3 , 0.96g / cm 3 , 0.98g / cm 3 , 1g / cm 3 , 1.1g / cm 3 , 1.15g / cm 3 , 1.18g / cm 3 , 1.2g / cm 3 , 1.22g / cm 3 , 1.24g / cm 3 , 1.26g / cm 3 , 1.28g / cm 3 or 1.31 g / cm 3 ).
[0055] In a second aspect, the present invention provides a thermal insulation gradient composite material with controllable surface density, which is prepared by the preparation method described in the first aspect of the present invention.
[0056] The present invention will be further described below by way of examples, but the protection scope of the present invention is not limited to these embodiments.
[0057] The hot-melt phenolic resin used in the following embodiments and comparative examples is a pre-polyphenolic resin RA-13S purchased from North Glass Institute (Tengzhou) Composite Materials Co., Ltd. that can melt at 40-90° C. and cure at 100-200° C.
[0058] Example 1
[0059] ① Weigh hot-melt phenolic resin, mica powder and zirconium diboride powder in proportion, stir and mix them evenly under heating conditions at 70° C. to obtain a premix, wherein the mass fraction of mica powder in the premix is 5wt%, and the mass fraction of zirconium diboride powder is 5wt%; spread the premix on release paper into a 0.5 mm thick film to obtain a mixed film.
[0060] ② Lay the mixed film on one side of a fiber preform (quartz fiber felt) with a size of 100 mm (length) × 100 mm (width) × 30 mm (thickness) and use a vacuum bag pressing process to impregnate the mixed film into one side of the quartz fiber felt. The processing temperature of the vacuum bag pressing process is 70°C, the vacuum degree is -0.08 MPa, and the processing time is 30 minutes; repeat this step until the impregnation thickness of the premix in the quartz fiber felt reaches 3 mm, and the impregnation is completed.
[0061] ③ After impregnation, the quartz fiber felt with a premix of 3 mm in thickness was cured at 180° C. for 8 h to obtain a fiber preform with controllable surface density.
[0062] ④ In-situ forming of phenolic aerogel inside the fiber preform with controllable surface density obtained in step ③, after vacuum impregnation, sol-gel process, solvent replacement and normal pressure drying, a heat insulation layer is formed, and the density of the heat insulation layer is 0.3g / cm 3, obtaining a thermal insulation gradient composite material with controllable surface density; the specific steps of step ④ are as follows: liquid phenolic resin, dimethyl sulfoxide (solvent) and ethyl sulfate (curing agent) are mixed and stirred until clear and transparent, and vacuum degassing is performed to obtain a phenolic resin solution; wherein the volume ratio of the liquid phenolic resin to the dimethyl sulfoxide is 1:4, and the amount of ethyl sulfate is 2% of the mass of the liquid phenolic resin; the fiber preform with controllable surface density is placed in the phenolic resin solution for vacuum impregnation for 30 minutes (the pressure of the vacuum impregnation is 5 kPa), and then in situ sol-gel in the phenolic resin solution at 100°C for 4 hours, and the obtained semi-finished product is immersed in anhydrous ethanol for solvent replacement, the anhydrous ethanol solvent is changed every 24 hours, the anhydrous ethanol is changed 4 times, and finally dried at 150°C at normal pressure for 12 hours to obtain a thermal insulation gradient composite material with controllable surface density.
[0063] Example 2
[0064] ① Weigh hot-melt phenolic resin, ethylene glycol, mica powder and zirconium diboride powder in proportion, stir and mix them evenly under heating conditions at 70° C. to obtain a premix, wherein the mass fraction of mica powder in the premix is 5wt%, the mass fraction of zirconium diboride powder is 5wt%, and the mass fraction of ethylene glycol is 10wt%; spread the premix on release paper as a 0.5 mm thick film to obtain a mixed film.
[0065] ② Lay the mixed film on one side of a fiber preform (quartz fiber felt) with a size of 100 mm (length) × 100 mm (width) × 30 mm (thickness) and use a vacuum bag pressing process to impregnate the mixed film into one side of the quartz fiber felt. The processing temperature of the vacuum bag pressing process is 70°C, the vacuum degree is -0.08 MPa, and the processing time is 30 minutes; repeat this step until the impregnation thickness of the premix in the quartz fiber felt reaches 3 mm, and the impregnation is completed.
[0066] ③ After impregnation, the quartz fiber felt with a premix of 3 mm in thickness was cured at 180° C. for 8 h to obtain a fiber preform with controllable surface density.
[0067] ④ In-situ forming of phenolic aerogel inside the fiber preform with controllable surface density obtained in step ③, after vacuum impregnation, sol-gel process, solvent replacement and normal pressure drying, a heat insulation layer is formed, and the density of the heat insulation layer is 0.3g / cm 3, obtaining a thermal insulation gradient composite material with controllable surface density; the specific steps of step ④ are as follows: liquid phenolic resin, dimethyl sulfoxide (solvent) and ethyl sulfate (curing agent) are mixed and stirred until clear and transparent, and vacuum degassing is performed to obtain a phenolic resin solution; wherein the volume ratio of the liquid phenolic resin to the dimethyl sulfoxide is 1:4, and the amount of ethyl sulfate is 2% of the mass of the liquid phenolic resin; the fiber preform with controllable surface density is placed in the phenolic resin solution for vacuum impregnation for 30 minutes (the pressure of the vacuum impregnation is 5 kPa), and then in situ sol-gel in the phenolic resin solution at 100°C for 4 hours, and the obtained semi-finished product is immersed in anhydrous ethanol for solvent replacement, the anhydrous ethanol solvent is changed every 24 hours, the anhydrous ethanol is changed 4 times, and finally dried at 150°C at normal pressure for 12 hours to obtain a thermal insulation gradient composite material with controllable surface density.
[0068] Example 3
[0069] ① Weigh hot-melt phenolic resin, ethylene glycol, mica powder and zirconium diboride powder in proportion, stir and mix them evenly under heating conditions at 70° C. to obtain a premix, wherein the mass fraction of mica powder, the mass fraction of zirconium diboride powder and the mass fraction of ethylene glycol are 5wt%, 5wt% and 20wt% respectively; spread the premix on release paper into a 0.5 mm thick film to obtain a mixed film.
[0070] ② Lay the mixed film on one side of a fiber preform (quartz fiber felt) with a size of 100 mm (length) × 100 mm (width) × 30 mm (thickness) and use a vacuum bag pressing process to impregnate the mixed film into one side of the quartz fiber felt. The processing temperature of the vacuum bag pressing process is 70°C, the vacuum degree is -0.08 MPa, and the processing time is 30 min; repeat this step until the impregnation thickness of the premix in the quartz fiber felt reaches 5 mm, and the impregnation is completed.
[0071] ③ After impregnation, the quartz fiber felt with a premix of 5 mm in thickness was cured at 180° C. for 8 h to obtain a fiber preform with controllable surface density.
[0072] ④ In-situ forming of phenolic aerogel inside the fiber preform with controllable surface density obtained in step ③, after vacuum impregnation, sol-gel process, solvent replacement and normal pressure drying, a heat insulation layer is formed, and the density of the heat insulation layer is 0.4g / cm 3, obtaining a thermal insulation gradient composite material with controllable surface density; the specific steps of step ④ are as follows: liquid phenolic resin, dimethyl sulfoxide (solvent) and ethyl sulfate (curing agent) are mixed and stirred until clear and transparent, and vacuum degassing is performed to obtain a phenolic resin solution; wherein the volume ratio of the liquid phenolic resin to dimethyl sulfoxide is 1:3, and the amount of ethyl sulfate is 2% of the mass of the liquid phenolic resin; the fiber preform with controllable surface density is placed in the phenolic resin solution and vacuum impregnated for 45 minutes (the pressure of vacuum impregnation is 5 kPa), and then in situ sol-gel is performed in the phenolic resin solution at 100°C for 4 hours, and the obtained semi-finished product is immersed in anhydrous ethanol for solvent replacement, the anhydrous ethanol solvent is changed every 24 hours, the anhydrous ethanol is changed 4 times, and finally dried at 150°C at normal pressure for 12 hours to obtain a thermal insulation gradient composite material with controllable surface density.
[0073] Example 4
[0074] ① Weigh hot-melt phenolic resin, silicon carbide powder and zirconium diboride powder in proportion, stir and mix them evenly under heating conditions at 70° C. to obtain a premix, in which the mass fraction of silicon carbide powder and the mass fraction of zirconium diboride powder in the premix are 10wt%, and 10wt% respectively; spread the premix on release paper into a 0.5 mm thick film to obtain a mixed film.
[0075] ② Lay the mixed film on one side of a fiber preform (quartz fiber felt) with a size of 100 mm (length) × 100 mm (width) × 30 mm (thickness) and use a vacuum bag pressing process to impregnate the mixed film into one side of the quartz fiber felt. The processing temperature of the vacuum bag pressing process is 70°C, the vacuum degree is -0.08 MPa, and the processing time is 30 min; repeat this step until the impregnation thickness of the premix in the quartz fiber felt reaches 5 mm, and the impregnation is completed.
[0076] ③ After impregnation, the quartz fiber felt with a premix of 5 mm in thickness was cured at 180° C. for 8 h to obtain a fiber preform with controllable surface density.
[0077] ④ In-situ forming of phenolic aerogel inside the fiber preform with controllable surface density obtained in step ③, after vacuum impregnation, sol-gel process, solvent replacement and normal pressure drying, a heat insulation layer is formed, and the density of the heat insulation layer is 0.4g / cm 3, obtaining a thermal insulation gradient composite material with controllable surface density; the specific steps of step ④ are as follows: liquid phenolic resin, dimethyl sulfoxide (solvent) and ethyl sulfate (curing agent) are mixed and stirred until clear and transparent, and vacuum degassing is performed to obtain a phenolic resin solution; wherein the volume ratio of the liquid phenolic resin to dimethyl sulfoxide is 1:3, and the amount of ethyl sulfate is 2% of the mass of the liquid phenolic resin; the fiber preform with controllable surface density is placed in the phenolic resin solution and vacuum impregnated for 45 minutes (the pressure of vacuum impregnation is 5 kPa), and then in situ sol-gel is performed in the phenolic resin solution at 100°C for 4 hours, and the obtained semi-finished product is immersed in anhydrous ethanol for solvent replacement, the anhydrous ethanol solvent is changed every 24 hours, the anhydrous ethanol is changed 4 times, and finally dried at 150°C at normal pressure for 12 hours to obtain a thermal insulation gradient composite material with controllable surface density.
[0078] Example 5
[0079] ① Weigh hot-melt phenolic resin, ethanol, silicon carbide powder and zirconium diboride powder in proportion, stir and mix them evenly under heating conditions at 70° C. to obtain a premix, in which the mass fraction of silicon carbide powder is 5wt%, the mass fraction of zirconium diboride powder is 15wt%, and the mass fraction of ethanol is 10wt%; spread the premix on release paper into a 0.5 mm thick film to obtain a mixed film.
[0080] ② Lay the mixed film on one side of a fiber preform (quartz fiber felt) with a size of 100 mm (length) × 100 mm (width) × 30 mm (thickness) and use a vacuum bag pressing process to impregnate the mixed film into one side of the quartz fiber felt. The processing temperature of the vacuum bag pressing process is 70°C, the vacuum degree is -0.08 MPa, and the processing time is 30 minutes; repeat this step until the impregnation thickness of the premix in the quartz fiber felt reaches 3 mm, and the impregnation is completed.
[0081] ③ After impregnation, the quartz fiber felt with a premix of 3 mm in thickness was cured at 180° C. for 8 h to obtain a fiber preform with controllable surface density.
[0082] ④ In-situ forming of phenolic aerogel inside the fiber preform with controllable surface density obtained in step ③, after vacuum impregnation, sol-gel process, solvent replacement and normal pressure drying, a heat insulation layer is formed, and the density of the heat insulation layer is 0.3g / cm 3, obtaining a thermal insulation gradient composite material with controllable surface density; the specific steps of step ④ are as follows: liquid phenolic resin, dimethyl sulfoxide (solvent) and ethyl sulfate (curing agent) are mixed and stirred until clear and transparent, and vacuum degassing is performed to obtain a phenolic resin solution; wherein the volume ratio of the liquid phenolic resin to the dimethyl sulfoxide is 1:4, and the amount of ethyl sulfate is 2% of the mass of the liquid phenolic resin; the fiber preform with controllable surface density is placed in the phenolic resin solution for vacuum impregnation for 30 minutes (the pressure of the vacuum impregnation is 5 kPa), and then in situ sol-gel in the phenolic resin solution at 100°C for 4 hours, and the obtained semi-finished product is immersed in anhydrous ethanol for solvent replacement, the anhydrous ethanol solvent is changed every 24 hours, the anhydrous ethanol is changed 4 times, and finally dried at 150°C at normal pressure for 12 hours to obtain a thermal insulation gradient composite material with controllable surface density.
[0083] Example 6
[0084] ① Weigh hot-melt phenolic resin, ethanol, silicon carbide powder and zirconium diboride powder in proportion, stir and mix them evenly under heating conditions at 70° C. to obtain a premix, in which the mass fraction of silicon carbide powder is 5wt%, the mass fraction of zirconium diboride powder is 15wt%, and the mass fraction of ethanol is 20wt%; spread the premix on release paper into a 0.5 mm thick film to obtain a mixed film.
[0085] ② Lay the mixed film on one side of a fiber preform (quartz fiber felt) with a size of 100 mm (length) × 100 mm (width) × 30 mm (thickness) and use a vacuum bag pressing process to impregnate the mixed film into one side of the quartz fiber felt. The processing temperature of the vacuum bag pressing process is 70°C, the vacuum degree is -0.08 MPa, and the processing time is 30 min; repeat this step until the impregnation thickness of the premix in the quartz fiber felt reaches 6 mm, and the impregnation is completed.
[0086] ③ After impregnation, the quartz fiber felt with a premix of 6 mm in thickness was cured at 180° C. for 8 h to obtain a fiber preform with controllable surface density.
[0087] ④ In-situ forming of phenolic aerogel inside the fiber preform with controllable surface density obtained in step ③, after vacuum impregnation, sol-gel process, solvent replacement and normal pressure drying, a heat insulation layer is formed, and the density of the heat insulation layer is 0.3g / cm 3, obtaining a thermal insulation gradient composite material with controllable surface density; the specific steps of step ④ are as follows: liquid phenolic resin, dimethyl sulfoxide (solvent) and ethyl sulfate (curing agent) are mixed and stirred until clear and transparent, and vacuum degassing is performed to obtain a phenolic resin solution; wherein the volume ratio of the liquid phenolic resin to the dimethyl sulfoxide is 1:4, and the amount of ethyl sulfate is 2% of the mass of the liquid phenolic resin; the fiber preform with controllable surface density is placed in the phenolic resin solution for vacuum impregnation for 30 minutes (the pressure of the vacuum impregnation is 5 kPa), and then in situ sol-gel in the phenolic resin solution at 100°C for 4 hours, and the obtained semi-finished product is immersed in anhydrous ethanol for solvent replacement, the anhydrous ethanol solvent is changed every 24 hours, the anhydrous ethanol is changed 4 times, and finally dried at 150°C at normal pressure for 12 hours to obtain a thermal insulation gradient composite material with controllable surface density.
[0088] Example 7
[0089] Example 7 is substantially the same as Example 4, except that:
[0090] ① Weigh hot-melt phenolic resin, silicon carbide powder and zirconium diboride powder in proportion, stir and mix them evenly under heating conditions at 70° C. to obtain a premix, in which the mass fraction of silicon carbide powder and the mass fraction of zirconium diboride powder in the premix are 15wt%, and 15wt% respectively; spread the premix on release paper into a 0.5 mm thick film to obtain a mixed film.
[0091] Example 8
[0092] Embodiment 8 is substantially the same as Embodiment 5, except that:
[0093] ① Weigh hot-melt phenolic resin, ethanol, silicon carbide powder and zirconium diboride powder in proportion, stir and mix them evenly under heating conditions at 70° C. to obtain a premix, in which the mass fraction of silicon carbide powder is 5wt%, the mass fraction of zirconium diboride powder is 15wt%, and the mass fraction of ethanol is 30wt%; spread the premix on release paper as a 0.5 mm thick film to obtain a mixed film.
[0094] Example 9
[0095] Example 9 is substantially the same as Example 4, except that:
[0096] ② Lay the mixed film on one side of a fiber preform (quartz fiber felt) with a size of 100 mm (length) × 100 mm (width) × 30 mm (thickness) and use a vacuum bag pressing process to impregnate the mixed film into one side of the quartz fiber felt. The processing temperature of the vacuum bag pressing process is 70°C, the vacuum degree is -0.08 MPa, and the processing time is 30 min; repeat this step until the impregnation thickness of the premix in the quartz fiber felt reaches 10 mm, and the impregnation is completed.
[0097] ③ After impregnation, the quartz fiber felt with a premix having an impregnation thickness of 10 mm was cured at 180° C. for 8 hours to obtain a fiber preform with controllable surface density.
[0098] Comparative Example 1
[0099] ① The hot-melt phenolic resin was melted at 70° C. and the melted hot-melt phenolic resin was spread on release paper as a 0.5 mm thick film to obtain a phenolic resin film.
[0100] ② Lay the phenolic resin film on one side of a fiber preform (quartz fiber felt) with a size of 100 mm (length) × 100 mm (width) × 30 mm (thickness) and use a vacuum bag pressing process to impregnate the phenolic resin film into one side of the quartz fiber felt. The processing temperature of the vacuum bag pressing process is 70°C, the vacuum degree is -0.08 MPa, and the processing time is 30 minutes; repeat this step until the impregnation thickness of the hot-melt phenolic resin in the quartz fiber felt reaches 3 mm, and the impregnation is completed.
[0101] ③ After impregnation, the quartz fiber felt with a hot-melt phenolic resin impregnation thickness of 3 mm was cured at 180° C. for 8 hours to obtain a fiber preform with controllable surface density.
[0102] ④ In-situ forming of phenolic aerogel inside the fiber preform with controllable surface density obtained in step ③, after vacuum impregnation, sol-gel process, solvent replacement and normal pressure drying, a heat insulation layer is formed, and the density of the heat insulation layer is 0.3g / cm 3 , obtaining a thermal insulation gradient composite material with controllable surface density; the specific steps of step ④ are as follows: liquid phenolic resin, dimethyl sulfoxide (solvent) and ethyl sulfate (curing agent) are mixed and stirred until clear and transparent, and vacuum degassing is performed to obtain a phenolic resin solution; wherein the volume ratio of the liquid phenolic resin to the dimethyl sulfoxide is 1:4, and the amount of ethyl sulfate is 2% of the mass of the liquid phenolic resin; the fiber preform with controllable surface density is placed in the phenolic resin solution for vacuum impregnation for 30 minutes (the pressure of the vacuum impregnation is 5 kPa), and then in situ sol-gel in the phenolic resin solution at 100°C for 4 hours, and the obtained semi-finished product is immersed in anhydrous ethanol for solvent replacement, the anhydrous ethanol solvent is changed every 24 hours, the anhydrous ethanol is changed 4 times, and finally dried at 150°C at normal pressure for 12 hours to obtain a thermal insulation gradient composite material with controllable surface density.
[0103] Comparative Example 2
[0104] Comparative Example 2 is substantially the same as Comparative Example 1, except that:
[0105] ② Lay the phenolic resin film on one side of a fiber preform (quartz fiber felt) with a size of 100 mm (length) × 100 mm (width) × 30 mm (thickness) and use a vacuum bag pressing process to impregnate the phenolic resin film into one side of the quartz fiber felt. The processing temperature of the vacuum bag pressing process is 70°C, the vacuum degree is -0.08 MPa, and the processing time is 30 minutes; repeat this step until the impregnation thickness of the hot-melt phenolic resin in the quartz fiber felt reaches 5 mm, and the impregnation is completed.
[0106] ③ After impregnation, the quartz fiber felt with a hot-melt phenolic resin impregnation thickness of 5 mm was cured at 180° C. for 8 hours to obtain a fiber preform with controllable surface density.
[0107] Comparative Example 3
[0108] Comparative Example 3 is substantially the same as Comparative Example 1, except that:
[0109] ④ In-situ forming of phenolic aerogel inside the fiber preform with controllable surface density obtained in step ③, after vacuum impregnation, sol-gel process, solvent replacement and normal pressure drying, a heat insulation layer is formed, and the density of the heat insulation layer is 0.4g / cm 3 , obtaining a thermal insulation gradient composite material with controllable surface density; the specific steps of step ④ are as follows: liquid phenolic resin, dimethyl sulfoxide (solvent) and ethyl sulfate (curing agent) are mixed and stirred until clear and transparent, and vacuum degassing is performed to obtain a phenolic resin solution; wherein the volume ratio of the liquid phenolic resin to dimethyl sulfoxide is 1:3, and the amount of ethyl sulfate is 2% of the mass of the liquid phenolic resin; the fiber preform with controllable surface density is placed in the phenolic resin solution and vacuum impregnated for 45 minutes (the pressure of vacuum impregnation is 5 kPa), and then in situ sol-gel is performed in the phenolic resin solution at 100°C for 4 hours, and the obtained semi-finished product is immersed in anhydrous ethanol for solvent replacement, the anhydrous ethanol solvent is changed every 24 hours, the anhydrous ethanol is changed 4 times, and finally dried at 150°C at normal pressure for 12 hours to obtain a thermal insulation gradient composite material with controllable surface density.
[0110] Comparative Example 4
[0111] ① Weigh the hot-melt phenolic resin, silicon carbide powder and zirconium diboride powder in proportion, stir and mix them evenly under heating conditions at 70° C. to obtain a premix, in which the mass fraction of silicon carbide powder is 10wt%, and the mass fraction of zirconium diboride powder is 10wt%.
[0112] ② The obtained premix is evenly coated on one side of a fiber preform (quartz fiber felt) with a size of 100 mm (length) × 100 mm (width) × 30 mm (thickness) and the premix is impregnated into one side of the quartz fiber felt using a vacuum bag pressing process. The processing temperature of the vacuum bag pressing process is 70°C, the vacuum degree is -0.08 MPa, and the processing time is 30 min; repeat this step until the impregnation thickness of the premix in the quartz fiber felt reaches 5 mm, and the impregnation is completed.
[0113] ③ The impregnated quartz fiber felt is cured at 180°C for 8 hours to obtain a fiber preform with controllable surface density.
[0114] ④ In-situ forming of phenolic aerogel inside the fiber preform with controllable surface density obtained in step ③, after vacuum impregnation, sol-gel process, solvent replacement and normal pressure drying, a heat insulation layer is formed, and the density of the heat insulation layer is 0.4g / cm 3 , obtaining a thermal insulation gradient composite material with controllable surface density; the specific steps of step ④ are as follows: liquid phenolic resin, dimethyl sulfoxide (solvent) and ethyl sulfate (curing agent) are mixed and stirred until clear and transparent, and vacuum degassing is performed to obtain a phenolic resin solution; wherein the volume ratio of the liquid phenolic resin to dimethyl sulfoxide is 1:3, and the amount of ethyl sulfate is 2% of the mass of the liquid phenolic resin; the fiber preform with controllable surface density is placed in the phenolic resin solution and vacuum impregnated for 45 minutes (the pressure of vacuum impregnation is 5 kPa), and then in situ sol-gel is performed in the phenolic resin solution at 100°C for 4 hours, and the obtained semi-finished product is immersed in anhydrous ethanol for solvent replacement, the anhydrous ethanol solvent is changed every 24 hours, the anhydrous ethanol is changed 4 times, and finally dried at 150°C at normal pressure for 12 hours to obtain a thermal insulation gradient composite material with controllable surface density.
[0115] This comparative example does not use the method of layer-by-layer coating of a single layer of film. Although the fiber preform can be impregnated, a large amount of premix will overflow from all sides due to the edge effect during impregnation, which on the one hand causes waste and on the other hand cannot uniformly control the impregnation thickness.
[0116] Comparative Example 5
[0117] Comparative Example 5 A ceramicizable heat-insulating composite material was obtained by referring to Example 2 of CN 116118222 A.
[0118] Comparative Example 6
[0119] Comparative Example 6 Referring to Example 1 of CN 105061981 B, a phenolic impregnated ceramic fiber skeleton composite material was obtained.
[0120] The present invention conducted density test and oxyacetylene test (heat flux density 1.5MW / m 2 , oxyacetylene test time is 300s), the results are shown in Table 1.
[0121] Table 1
[0122]
[0123]
[0124] In Table 1, the symbol “-” indicates that the performance test was not conducted or the performance indicator does not exist.
[0125] From the results in Table 1, it can be found that with the addition of solvent content, the density of the dense layer of the composite material decreases, and with the increase of ceramic filler content, the density of the dense layer of the composite material increases. Therefore, the density of the surface dense layer can be regulated by adjusting the addition ratio of ceramic filler and solvent in the mixed film, so that targeted design can be carried out according to the service environment. At the same time, the anti-insulation gradient composite materials with controllable surface density prepared in all embodiments of the present invention have excellent anti-insulation performance and anti-ablation performance.
[0126] Parts of the present invention that are not described in detail are well known to those skilled in the art.
[0127] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or make equivalent replacements for some of the technical features therein. However, these modifications or replacements do not deviate the essence of the corresponding technical solutions from the spirit and scope of the technical solutions of the embodiments of the present invention.
Claims
1. A method for preparing a thermal insulation gradient composite material with controllable surface density, characterized in that: The method comprises the following steps: (1) Mixing a hot-melt phenolic resin, a ceramic filler and a solvent at 40-90° C. to obtain a premix, and coating the premix on a release paper using a coating machine to obtain a mixed film; the hot-melt phenolic resin is a prepolymerized phenolic resin that can melt at 40-90° C. and solidify at 100-200° C.; the mass fraction of the ceramic filler in the premix is 1-30wt%; the solvent is ethanol and / or ethylene glycol; the mass fraction of the solvent in the premix is 5-30wt%; (2) Laying the mixed film on one side of the fiber preform and impregnating the mixed film into the fiber preform by using a vacuum bag pressing process; repeating this step until the premix impregnated in the fiber preform reaches a preset impregnation thickness, and the impregnation is completed; the processing temperature of the vacuum bag pressing process is 40-90°C, the vacuum degree is -0.03-0.1MPa, and the processing time is 5-60min; (3) curing the impregnated fiber preform at 100-200° C. to obtain a fiber preform with controllable surface density; (4) preparing a phenolic resin solution, then impregnating a fiber preform with controllable surface density with the phenolic resin solution, and then sequentially subjecting the preform to sol-gel, solvent replacement and normal pressure drying to obtain a thermal insulation gradient composite material with controllable surface density; wherein liquid phenolic resin, dimethyl sulfoxide and ethyl sulfate are mixed and stirred until clear and transparent and vacuum degassed to obtain a phenolic resin solution.
2. The preparation method according to claim 1, characterized in that: The ceramic filler is at least one of a silicon-based filler, a boron-based filler, a carbon-based filler and an oxide-based filler; The particle size of the ceramic filler is 0.1-10 μm.
3. The preparation method according to claim 1, characterized in that: The ceramic filler is at least one of mica, zirconium diboride, boron carbide and silicon carbide.
4. The preparation method according to claim 1, characterized in that: The thickness of the mixed film is 0.1-2 mm.
5. The preparation method according to claim 1, characterized in that: The impregnation thickness of the premix in the fiber preform is 1-10 mm.
6. The preparation method according to claim 1, characterized in that: The fiber preform is at least one of a carbon fiber preform, a quartz fiber preform, a mullite fiber preform, and a glass fiber preform.
7. The preparation method according to claim 1, characterized in that: The structure of the fiber preform is at least one of fiber needle felt, 2.5D fabric, and 3D fabric.
8. The preparation method according to claim 1, characterized in that: The curing time is 2 to 10 hours.
9. The preparation method according to claim 1, characterized in that: The anti-heat-insulation gradient composite material with controllable surface density comprises a density gradient structure composed of a dense layer and a heat-insulating layer formed in a fiber preform; The density of the thermal insulation layer is 0.2-0.5 g / cm 3 ; The density of the dense layer is 0.89-1.31 g / cm 3 .
10. A thermal insulation gradient composite material with controllable surface density obtained by the preparation method according to any one of claims 1 to 9.
Citation Information
Patent Citations
A kind of phenolic formaldehyde impregnated ceramic fiber skeleton composite material and preparation method thereof
CN105061981B
Ceramic heat-proof and heat-insulating composite material and preparation method thereof
CN116118222A